Engaging Migrants in Translocal Partnerships: the Case of Dutch–Moroccan and Dutch–Turkish Municipal Partnerships. Issue 4 (22nd August 2014) - van Ewijk, Edith
Abstract: From 2000 onwards, Dutch local governments have established transnational partnerships with local governments in Morocco and Turkey, two main migrant source countries to the Netherlands. These municipal partnerships aim at strengthening and transforming local governance on both sides of the partnerships. This is particularly relevant as roles of local governments in Morocco and Turkey are changing because of decentralisation and democratisation processes, whereas Dutch municipalities face challenges related to ethnic and cultural diversity. This paper seeks to answer two questions: first, what roles migrants play within these partnerships, and second, how the involvement of migrants influences the process of knowledge exchange and mutual learning leading to changes in local governance. The paper is based on a case study approach including five municipal partnerships and contributes both to the scarce body of knowledge about the roles of migrants in transnational cooperation at the local level and to the limited research on mutual learning in municipal partnerships. The research shows migrants fulfil several roles; they act as initiators, key actors, facilitators, and contributors of specialised and cultural knowledge. Their role as facilitators in the exchanges focusing at the interfaces between local governments and citizens is particularly relevant as introducing youth participation is new in the involved municipalities in Morocco and dealing with cultural diversity is a continuing challenge in the Dutch municipalities. There still is a large untapped potential as limited use is made of involving larger groups of migrants and on drawing on their networks. Copyright © 2014 John Wiley & Sons, Ltd.